Jan Cep and Milada Souckova: Two Modes of Nostalgia - Hrdlicka, Josef (Bohemica Olomucensia, 2015)
The article shortly describes more general aspects of the writing in exile, especially in regard to the concept of nostalgia studied by Jean Starobinski. It examines the nostalgia by Jan Cep and Milada Souckova and investigates the conception of ``writing for one's self '' as an important characteristic not only in exilic writing.
Keywords: Jan Cep; Milada Souckova; nostalgia; exilic writing